Displacing the Christian Theodicy of Hell: Yi Kwangsu’s Search for the Willful Individual in Colonial Modernity - Jun-Hyeok Kwak; Mengxiao Huang (Religions)
This article aims to offer Yi Kwangsu’s The Heartless (Mujŏng, 1917), the first modern Korean novel, as an emblem of hybrid religiosity in colonial modernity that sheds light on an ambivalent alterity in the problem of hell in non-Western cultures. To the extent that the problem of hell in Christianity pertains to the question of why God allows evil to exist eternally, God’s omnipotent authority with justice and fairness beyond the grave is placed at the center of the inquiry into the ultimate standard of moral goodness the religious feasibility of which justifies the existence of sinners suffering eternal damnation in hell. But the co-existence of the omnipotent God and unrepentant sinners is not always questioned in the religiosity of hell in non-Western cultures. The Christian imaginary of hell in non-Western cultures often demarcates the question of God’s sovereignty from the sufferings of sinners in the problem of hell. Based on these observations, this article will investigate Yi’s narratives of hell in The Heartless, which are associated with Christianity but intertwined with his ethical demands for shaping a new individuality beyond the traditional hybrid religiosity of hell. Specifically, first, we will show that Yi’s Christian imaginary of hell is reformulated through the traditional imaginaries of hell in which, regardless of the existence of God’s sovereignty over the created order, the sufferings of sinners in hell function to secure social norms and orders. In doing so, we claim that the Christian imaginary of hell in The Heartless is relegated to a rhetorical means to beget the need for the self-awakening of the inner-self through which individual desires can be freed from the influences of Confucian morality as well as Christian theodicy. Second, in comparison with Lu Xun’s sympathetic relocation of Christian spirituality within the traditional Chinese imaginaries of hell in his longing for modern subjectivity, we explore Yi’s hybrid religiosity within colonial modernity, the vitality of which cannot be confined within the simple dichotomy between Western and non-Western cultures. At this juncture, the upshot of Yi’s hybrid religiosity within colonial modernity is that the theodicy of hell in Christianity can be displaced and thereby disenfranchised from the centrality of the search for a new individuality.